2018
DOI: 10.1093/brain/awx373
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for verbal memory enhancement with electrical brain stimulation in the lateral temporal cortex

Abstract: Direct electrical stimulation of the human brain can elicit sensory and motor perceptions as well as recall of memories. Stimulating higher order association areas of the lateral temporal cortex in particular was reported to activate visual and auditory memory representations of past experiences (Penfield and Perot, 1963). We hypothesized that this effect could be used to modulate memory processing. Recent attempts at memory enhancement in the human brain have been focused on the hippocampus and other mesial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 26 publications
8
69
0
Order By: Relevance
“…An open and important question is whether such stimulation can be used to enhance cognitive function, and if so, whether stimulation parameters (e.g., intensity and location) can be optimized and personalized based on individual brain anatomy and physiology. While some studies demonstrate enhancements in spatial learning [39] and memory [19,38,18,37,66] following direct electrical stimulation, others show decrements [30]. Such conflicting evidence is also present in the literature surrounding other types of stimulation, including transcranial magnetic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…An open and important question is whether such stimulation can be used to enhance cognitive function, and if so, whether stimulation parameters (e.g., intensity and location) can be optimized and personalized based on individual brain anatomy and physiology. While some studies demonstrate enhancements in spatial learning [39] and memory [19,38,18,37,66] following direct electrical stimulation, others show decrements [30]. Such conflicting evidence is also present in the literature surrounding other types of stimulation, including transcranial magnetic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our results suggest a means for biologically monitoring the tuning of therapeutic electrical stimulation in the treatment of several neurological disorders (28,29), such as epilepsy (17,(30)(31)(32), sleep and memory dysfunction (33)(34)(35), brain tumors (36) and Parkinson disease (37). It has been noted empirically that the frequency of electrical stimulation is a critical determinant of outcome in treating particular neurological diseases.…”
mentioning
confidence: 99%
“…In the first study of its kind, applying an integrated IEEG-fMRI method, we have shown that established markers of memory encoding correspond to meaningful network differences captured by rsfMRI. In clinical terms, knowing a region is a hub, playing an important role in multi-regional and multi-functional connectivity, may inform technologies trying to identify the most effective targets to electrically or pharmacologically stimulate for cognitive enhancement in areas such as memory Ezzyat Y et al, 2018;Kucewicz MT et al, 2018), or perhaps be used to identify the areas with sufficient influence over targets to generate effective neuro-feedback loops (Hohenfeld C et al, 2017;Murphy AC et al, 2017).…”
Section: Discussionmentioning
confidence: 99%